2015
DOI: 10.1139/cjm-2014-0734
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri glyceraldehyde-3-phosphate dehydrogenase functions in adhesion to intestinal epithelial cells

Abstract: This study was aimed to identify key surface proteins mediating the adhesion of lactobacilli to intestinal epithelial cells. By using Caco-2 and IPEC-J2 cells labeled with sulfo-NHS-biotin in the western blotting, a protein band of an approximately 37 kDa was detected on the surface layer of Lactobacillus reuteri strains ZJ616, ZJ617, ZJ621, and ZJ623 and Lactobacillus rhamnosus GG. Mass spectrometry analysis using the adhesion-related protein from L. reuteri ZJ617 showed that it was 100% homologous to the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…Glyceraldehyde-3-phosphate dehydrogenase is an important enzyme in the glycolytic pathway responsible for the conversion of glyceraldehyde 3-phosphate to D -glycerate 1,3-bisphosphate in the cytoplasm. Recently, many reports have confirmed that GAPDH is also located on the surface of many bacteria, such as Lactobacillus reuteri ( Zhang W.M. et al, 2015 ), Lactobacillus jensenii ( Spurbeck and Arvidson, 2010 ), and L. plantarum ( Saad et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyceraldehyde-3-phosphate dehydrogenase is an important enzyme in the glycolytic pathway responsible for the conversion of glyceraldehyde 3-phosphate to D -glycerate 1,3-bisphosphate in the cytoplasm. Recently, many reports have confirmed that GAPDH is also located on the surface of many bacteria, such as Lactobacillus reuteri ( Zhang W.M. et al, 2015 ), Lactobacillus jensenii ( Spurbeck and Arvidson, 2010 ), and L. plantarum ( Saad et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous reports have shown that surface GAPDH can adhere to mucus components, and extracellular matrices, such as fibronectin, laminin, and collagen. A study have found that GAPDH existed on the surface of Lactobacillus casei under acidic conditions ( Zhang W.M. et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…SingalP prediction revealed that both DLD1 and DLD2 had no typical signal peptide. Similar to glyceraldehyde-3-phosphate dehydrogenase in Lactobacillus reuteri [40], DLDs are also located on the cell surface of V. splendidus without a typical signal peptide. Smart analysis showed that both DLD1 and DLD2 contained a Pyr_redox domain and GIDA domain.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that IPEC-J2 cells may induce the expression of these proteins in LM1, then confer higher adhesion capability of LM1 because these proteins were also observed in other adherent Lactobacillus species ( Kinoshita et al, 2008a ; Dhanani and Bagchi, 2013 ; Kainulainen and Korhonen, 2014 ). These proteins, originally found in the cytoplasm, were also identified to be moonlighting proteins, which are found extracellularly and can mediate bacterial establishment to IECs ( Granato et al, 2004 ; Zhang et al, 2015 ; Derkaoui et al, 2016 ). In a previous study, it was shown that EF-Tu on the surface of L. johnsonii La1 improved binding to intestinal cells and mucins ( Granato et al, 2004 ), which might also participate in gut homeostasis by binding with the intestinal epithelia and maintaining barrier structure and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that EF-Tu on the surface of L. johnsonii La1 improved binding to intestinal cells and mucins ( Granato et al, 2004 ), which might also participate in gut homeostasis by binding with the intestinal epithelia and maintaining barrier structure and integrity. GAPDH also facilitated the binding of several strains of lactobacilli to colonic Caco-2 cells and human ABO-blood type antigens ( Kinoshita et al, 2008b ; Zhang et al, 2015 ). In addition, GAPDH may also possess antigenic and immunomodulatory properties that has the potential to induce B and T cell activation or increase IL-10 production in the host ( Kainulainen and Korhonen, 2014 ).…”
Section: Discussionmentioning
confidence: 99%